Pro-Self-Harm and the Visibility of Youth-Generated Problematic Content - boyd, danah; Ryan, Jenny; Leavitt, Alex (I/S: A Journal of Law and Policy for the Information Society, 2011)
The increasing ubiquity of the Internet in the everyday lives of youth has been accompanied by a whole new set of anxieties and concerns. While many have worried about how the Internet increases youth access to problematic content—including pornographic and violent content—little consideration has been paid to youth-generated problematic content. This article examines one genre of youth-generated problematic content: that which advocates self-harm practices. Countless websites and online communities are devoted to the topic of deliberate self-harm, ranging from online therapy and support groups to ―pro-anorexia‖ and ―pro-cutting‖ websites, and much of the content on these websites is produced by and for youth. This paper seeks to provide an overview of what is known about the spectrum of self-harm practices and how technology inflects these practices in new ways. We begin with a brief introductory section detailing a working definition of self-harm based on the most recent published literature, outline the general prevalence and demographics, and note the correlations between self-harm practices, eating disorders, and the media. The latter half of this article summarizes various approaches to handling online self-harm content, ranging from censoring content (through Internet Service Provider (ISP) policies and governmental regulations) to providing support for those struggling with the underlying issues associated with deliberate self-harm (e.g., media literacy programs, online support groups, and grassroots social movements and campaigns). Given that censorship of such content often results in pushing it further underground, we recommend solutions that address the underlying sociocultural forces that motivate youth to engage in self-harm practices, and call for further research into these phenomena.